INFLUENCE OF INFORMATION TECHNOLOGY ON INTERNAL CONTROL SYSTEMS IN TERTIARY INSTITUTIONS IN OSUN STATE, NIGERIA (Malaysian Management Journal, 2024)
The study examined how information technology affects internal control systems in tertiary institutions in Osun State. Specific goals were to ascertain whether or not information technology has a significant impact on the internal control systems and internal audit processes of tertiary institutions. A survey research design was chosen. A sample size of 100 respondents participated in the study. This study used the stratified sampling method and a regression technique was used for data analysis. The findings showed that internal control systems and internal audit procedures in tertiary institutions in Osun State were highly influenced by information technology with t= 20.02 P< 0.0 and t= 19.049p